PENGGAMBARAN KEPERCAYAAN SEKALA DAN NISKALA DI MASYARAKAT BALI PADA FILM “THE SEEN AND UNSEEN” - Ayuni Widya Kusuma Wardhani; Elda Franzia (Universitas Trisakti, 2020)
Abstract The Visualization of Balinese Society’s Sekala and Niskala Beliefs in “The Seen and Unseen” Movie. Art and culture are the inspiration for filmmakers in their work. The diversity of traditions and culture in Indonesia has become something people take interest in to be in a film work. This research discusses the visualization of sectarian beliefs in Balinese society in the “The Seen and Unseen” movie. Through the semiotic method, analysis of scenes that depicts beliefs of the sekala and niskala are done. This analysis is translated into Roland Barthes’s semiotic theory through the meaning of denotation, connotation, and myth. Sekala and niskala are Balinese beliefs that are very inherent in everyday life that have visible and invisible meanings. This belief guides Balinese people to live a balanced life. In the film “The Seen and Unseen” this belief is depicted with an egg symbol, banging twins, moon, day and night. The result of this research is the understanding of those symbols and meanings in “The Seen and Unseen” movie. Abstrak Penggambaran Kepercayaan Sekala dan Niskala di Masyarakat Bali pada Film “The Seen and Unseen”. Seni dan budaya merupakan inspirasi bagi sineas dalam berkarya. Keberagaman tradisi dan budaya di Indonesia menjadi sesuatu yang menarik untuk diangkat menjadi sebuah karya film. Penelitian ini membahas tentang penggambaran kepercayaan sekala dan niskala di masyarakat Bali pada film “The Seen and Unseen”. Melalui metode semiotika dilakukan analisis terhadap adegan-adegan yang menggambarkan kepercayaan sekala dan niskala. Analisis dijabarkan dengan teori semiotika Roland Barthes melalui makna denotasi, konotasi, dan mitos. Sekala dan niskala merupakan kepercayaan masyarakat Bali yang sangat melekat dalam kehidupan sehari-hari yang memiliki makna terlihat dan tidak terlihat. Kepercayaan tersebut mengarahkan masyarakat Bali agar menjalani kehidupan yang seimbang. Dalam film “The Seen and Unseen” ini kepercayaan sekala dan niskala digambarkan dengan simbol telur, kembar buncing, bulan, siang dan malam. Hasil dari penelitian ini adalah pemahaman terhadap tanda-tanda tersebut yang dihadirkan pada film “The Seen and Unseen”. Kata kunci: film, budaya, tradisi, sekala dan niskala, Bali